Analisis Kesulitan Belajar Operasi Hitung Pembagian Matematika Kelas IV SD N 03 Sambung Kabupaten Grobogan - Annisak Miftakhul Hidayah; Sumarno Sumarno; Ferina Agustini (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
What prompted this research was the discovery of difficulties experienced by students in solving math class IV questions on arithmetic operations material. The problem of this research was the difficulties experienced by students in completing arithmetic division operations and the factors that caused students to experience learning difficulties in division arithmetic operations.  The purpose of this study was to find out the difficulties experienced by class IV students at SDN 03 Sambung in Grobogan Regency in completing arithmetic division operations and to find out the factors that cause students to experience learning difficulties in arithmetic operations in grade IV at SDN 03 Sambung in Grobogan Regency.  This type of research is descriptive qualitative.  Based on the results of the research findings, fourth grade students at SDN 03 Sambung in Grobogan Regency experienced difficulties in working on math problems on arithmetic operations on division.  Using test methods, interviews, and questionnaires.  The results of this study were the fourth grade students at SDN 03 Sambung in Grobogan Regency, with a total of 19 students who experienced difficulties.  In the study, there were research questionnaire findings in the "Never" category.